Genotoxic impacts of long term exposure of Arsenic and Fluoride to Cat Fish, Clarias batrachus - Mishra, Purva; Poddar, Aditi Niyogi (International Journal of Scientific Research in Biological Sciences, 2021)
Arsenic and Fluoride are very common ground water pollutants, contributed by natural and anthropogenic sources leading to serious health effects in both terrestrial and aquatic organisms. The current research was carried out to identify the relationship between arsenic and fluoride, using Clarias batrachus (common cat fish) as an experimental model. The study includes seven groups (Group I to VII), one control (Group I) and other six (Group II, III, IV, V, VI, VII) exposed to different concentration of arsenic and fluoride individually and in combination. Long term exposure of 60 days was carried out for each group, with no toxicant added in Group I. Blood samples were collected from each experimental group on 60th day and COMET assay was performed to check genotoxicity. Parameters like Head DNA percentage, tail DNA Percentage, comet length, tail moment were calculated from comet images. Results revealed maximum DNA damage in group V, which was exposed to arsenic alone, concluding arsenic being more toxic than fluoride. Also, antagonistic relationship was established between arsenic and fluoride.